2017
DOI: 10.1016/j.medici.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Subjective visual vertical assessment with mobile virtual reality system

Abstract: The mobile virtual reality based system for implementation of subjective visual vertical test, is accurate and applicable in the clinical environment. The gamepad-based virtual object control method was preferred by the users. The tests were well tolerated with low dizziness scores in the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…The System Usability Scale (SUS) [42] is an instrument that allows usability practitioners and researchers to measure the subjective usability of products and services. In the VR domain, SUS has been utilised in several studies around such topics as VR rehabilitation and health services [54][55][56][57][58], VR learning [59], and VR training [60]. SUS is a ten-item questionnaire that can be administered quickly and easily, and it returns scores ranging from 0 to 100.…”
Section: Questionnaires Andmentioning
confidence: 99%
“…The System Usability Scale (SUS) [42] is an instrument that allows usability practitioners and researchers to measure the subjective usability of products and services. In the VR domain, SUS has been utilised in several studies around such topics as VR rehabilitation and health services [54][55][56][57][58], VR learning [59], and VR training [60]. SUS is a ten-item questionnaire that can be administered quickly and easily, and it returns scores ranging from 0 to 100.…”
Section: Questionnaires Andmentioning
confidence: 99%
“…SUS is an instrument that allows usability practitioners and researchers to measure the subjective usability of products and services. In the VR domain, SUS has been utilised in several studies around such topics as VR text input [23], VR rehabilitation and health services [32][33][34][35][36], VR learning [37] and VR training [38]. Specifically, it is a ten-item questionnaire that can be administered quickly and easily, and it returns scores ranging from 0-100.…”
Section: Demographics and Questionnairesmentioning
confidence: 99%
“…1,2,8,9 Sensitive measurement techniques have been required to evaluate the central and peripheral vestibular system function in patients with neurological disorders. 5,10 On the other hand, many studies reported that an evaluation of the balance function and visual system could be used to evaluate the vestibular function, even when a direct evaluation of the vestibular system was not included. [11][12][13][14] The subjective visual vertical (SVV) is a tool for evaluating the function of the utricle in the inner ear and aims to assess the perception of verticality or abnormally tilted visual sensation.…”
Section: Introductionmentioning
confidence: 99%